Engaging with the community: creating health awareness in Bukit Badong - Mansor, Masaany; Zahari, Muhammad Nur Islam (Faculty of Medicine, 2023)
On Saturday, 27th of May 2023, the Department of Otorhinolaryngology, Head and Neck Surgery (ORL-HNS) took one step further, leaving the comforts of our typical hospital working environment and weekend to engage with the workers of Gamuda Water Treatment Plant and their family members in Bukit Badong